Calculation of Parameters and Design of the Movable Transfer Station with Vibrating Screen Feeder for the Conveyor System of Deep Queries - SÅ‚adkowski, Aleksander; Yudin, Arkadiy; Komissarov, Anatoliy; Lagunova, Yuliya; Akhmetova, Madinur; Stolpovskikh, Ivan (International Journal of Engineering and Technology, 2018)
The paper considers a new design of the movable vibrating screen feeder KVG-1PS designed for the reception and transfer of rocks and ores in conveyor complexes of cyclic-and-continuous technology in open-cast mining. It contains the results of design analysis of the new mining machine. The paper represents the technique of establishing the main parameters and the calculation of the movable vibrating feeder on the basis of a cascade shock-absorbing system at the representation of the machine within a three-mass oscillatory system.Â